PERBANDINGAN PERJANJIAN KREDIT DALAM PRESPEKTIF PERJANJIAN SYARIAH ISLAM DAN KITAB UNDANG-UNDANG HUKUM PERDATA - RAHMAD NAULI SIREGAR (PREMISE LAW JURNAL, 2013)
The legal provision of credit agreement in syariah bank is Law No.21/2008 on Syariah Banking, Law No. 72/1992 on Profit-Sharing Bank, the Indonesian Civil Codes, Law No. 10/1998 on the Amendment of Law No. 7/1992 on Banking, the Regulation of Bank Indonesia, and the Fatwa of National Syariah Council related to syariah banking, while the legal provision of credit agreement in conventional bank is referred to Law No.10/1998 on the Amendment of Law No. 7/1992 on Banking, and the Indonesian Civil Codes. The form of the clause of financing agreement in syariah bank and credit agreement in conventional bank is substantially similar because both of them are standard written agreement and both agreements contain the amount of money, the amount of interest (conventional bank) or share of revenue (syariah bank), method of payment, repayment period and collateral in the form of land documents dan the evidence of vehicle ownership. The financing agreement is not different from the credit agreement in conventional bank because it refers to the Indonesian Civil Codes found in Book III on General Bonding. Therefore, the relationship between the agreement in syariah and conventional banks is close enough and subject to the same regulation of legislation. Keywords: Financing, Credit Agreement, Syariah Banking